Awakenings [videorecording (DVD)] - De Niro, Robert; Williams, Robin, 1951-2014; Heard, John, 1946-2017; Kavner, Julie; Miller, Penelope Ann; Sydow, Max von, 1929-2020-; Meara, Anne; Sacks, Oliver, 1933-2015 (Distributed by Image Entertainment, 1997)
Dr. Malcolm Sayer (Robin Williams) is a shy research physician who uses an experimental drug to "awaken" the catatonic victims of a rare disease. The awakening of the first patient proves a rebirth for the doctor, too, as the patient reveals life's simple but sweet pleasures to the introverted doctor. Encouraged by Leonard's stunning recovery, Sayer administers the drug to other patients.